2011
DOI: 10.1038/ng.998
|View full text |Cite
|
Sign up to set email alerts
|

Dense genotyping identifies and localizes multiple common and rare variant association signals in celiac disease

Abstract: We densely genotyped, using 1000 Genomes Project pilot CEU and additional re-sequencing study variants, 183 reported immune-mediated disease non-HLA risk loci in 12,041 celiac disease cases and 12,228 controls. We identified 13 new celiac disease risk loci at genome wide significance, bringing the total number of known loci (including HLA) to 40. Multiple independent association signals are found at over a third of these loci, attributable to a combination of common, low frequency, and rare genetic variants. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
703
1
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 737 publications
(734 citation statements)
references
References 40 publications
7
703
1
8
Order By: Relevance
“…Besides the detection of APOE and the 5q33.3 locus, longevity GWAS have been relatively unsuccessful and have failed to reveal novel associations with genome‐wide significance or sufficient reproducibility (Deelen et al ., 2011, 2014; Nebel et al ., 2011). Here, we performed a large‐scale candidate gene study by targeting established immune‐associated loci present on the Immunochip (Trynka et al ., 2011). The Immunochip was designed to perform fine‐mapping of GWAS loci of major immune‐mediated diseases using data from the 1000 Genomes Project and other sequencing initiatives.…”
mentioning
confidence: 99%
“…Besides the detection of APOE and the 5q33.3 locus, longevity GWAS have been relatively unsuccessful and have failed to reveal novel associations with genome‐wide significance or sufficient reproducibility (Deelen et al ., 2011, 2014; Nebel et al ., 2011). Here, we performed a large‐scale candidate gene study by targeting established immune‐associated loci present on the Immunochip (Trynka et al ., 2011). The Immunochip was designed to perform fine‐mapping of GWAS loci of major immune‐mediated diseases using data from the 1000 Genomes Project and other sequencing initiatives.…”
mentioning
confidence: 99%
“…More recently, the immunochip genotyping array has fine-mapped these regions and reported additional 13 susceptibility loci. 4 Many of the 39 non-HLA regions associated with the genetic risk to CD development are also shared with other autoimmune diseases; in particular, type 1 diabetes and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…The finemapping immunochip study revealed a major association peak spanning 2 kb (chr6: 128 332-128 335 kb) marked by rs55743914 (in the 3 0 -UTR of PTPRK) and a broader secondary signal (chr6: 128 307-128 339 kb) marked by rs72975916, tipping the scale in favor of PTPRK. 4 However, no functional confirmation of these candidate genes has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…3,12,13 Genome-wide significant association to celiac disease has recently been reported for markers in the CIITA gene. 14 In addition, increased susceptibility to myocardial infarction (MI), rheumatoid arthritis (RA) and multiple sclerosis (MS) has been demonstrated for a polymorphism (rs3087456) in the 5 0 region of type III CIITA. 15 However, this association has not always been replicated in later studies, and the outcome of the analysis is varying depending on which control group that has been used.…”
Section: Introductionmentioning
confidence: 99%